2024
DOI: 10.1038/s41467-024-48850-9
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)/Pd(IV) redox shuttle to suppress vacancy defects at grain boundaries for efficient kesterite solar cells

Jinlin Wang,
Jiangjian Shi,
Kang Yin
et al.

Abstract: Charge loss at grain boundaries of kesterite Cu2ZnSn(S, Se)4 polycrystalline absorbers is an important cause limiting the performance of this emerging thin-film solar cell. Herein, we report a Pd element assisted reaction strategy to suppress atomic vacancy defects in GB regions. The Pd, on one hand in the form of PdSex compounds, can heterogeneously cover the GBs of the absorber film, suppressing Sn and Se volatilization loss and the formation of their vacancy defects (i.e. VSn and VSe), and on the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…Previous reports have shown that Cu + –Sn 4+ -based solutions have great advantages in the fabrication of high-quality CZTSSe absorbers due to the unique direct phase transformation crystallization mechanism. 5,21,22 Introducing Ag + or Cd 2+ into kesterite through Cu + –Sn 4+ based DMSO solution has shown great success in precise control of alloying concentration, suppressing deep defects/band tailing, and improving device performance. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that Cu + –Sn 4+ -based solutions have great advantages in the fabrication of high-quality CZTSSe absorbers due to the unique direct phase transformation crystallization mechanism. 5,21,22 Introducing Ag + or Cd 2+ into kesterite through Cu + –Sn 4+ based DMSO solution has shown great success in precise control of alloying concentration, suppressing deep defects/band tailing, and improving device performance. 23,24…”
Section: Introductionmentioning
confidence: 99%